Studies in the History of Parliaments - Bardach, Juliusz (Czasopismo Prawno-Historyczne, 1984)
Recenzja: Studies in the History of Parliaments, Legislative Studies Quarterly, t. VII, z. 2, maj 1982. Wydawca: Comparative Legislative Research Center of the University of Iowa, s. 161-315.